Effect of Computer Graphics Instrucional Mode on Secondary School Stidents' Achievement in Civic Education - Olori Abiola Lateef; Ogunsanya Adeola Oladele (University of Sofia, 2022)
The study examined effect of computer graphics instructional mode on senior secondary school students' achievement in civic education. Three null hypotheses were drawn to guide the study. The study adopted a pre-test, post-test, control group quasi-experimental design. Purposive sampling techniques was used to select the sample size of 110 participants of two intact classes that form the control and experimental groups. The instruments used for data collection was an adopted Civic Education Achievement Test (CEAT). Data collected were statistically analyzed with Mean and Standard Deviation, Analysis of Covariance (ANCOVA) and T-test at 0.5 significant level. Finding from the study revealed that: there was significant difference in the pre-test and post- test mean score of students exposed to computer graphics instructional mode and those exposed to expository method (F 1,110 =52.743,df =1, P< 0.05 and sig =.000); there was significant difference between the academic achievements of students taught using computer graphics instructional mode and those taught using the expository method (Means 15.69, SD =1.701, t = 18.499, df = 108, p 0.000) and there was no significant difference between academic achievement of male and female students taught or exposed to computer graphics instructional mode (mean =15.53, SD = 1.778), t = 0.617,df = 56, p .538). Based on the findings it was recommended that computer graphics instructional mode should be used for teaching at secondary school.